Остракоды рода Ilyocypris Brady et Norm., 1889 в фауне Украины - Голубничая, Л.В. (Вестник зоологии, 1973)
The article deals with ecological and morphological data on representatives of the genus Ilyocypris — I. gibba, I. biplicata, I. bradyi, I. decipiens, 1. getica found by the author in the territory of the Ukraine. I. getica is mentioned for the fauna of the USSR for the first time.